ANALISIS NILAI TAMBAH EKONOMI (Economy Value Added) UNTUK MENGUKUR KINERJA KEUANGAN PETANI MINYAK KAYU PUTIH DESA PELA DAN BATU JUNGKU DI WILAYAH KERJA KESATUAN PENGELOLAAN HUTAN PRODUKSI (KPHP) MODEL UNIT III WAE TINA - WillY Marthen Behuku; Agustinus Kastanya; D V Pattimahu (JURNAL HUTAN PULAU-PULAU KECIL, 2016)
Eucalyptus oil venture which developed in the working area of Production Forest Management Unit (KPHP) Model Unit III Wae Tina, is one of the livelihood for generations have grown by farmers white wood craftsmen. In conducting the research study analyzes the economic value added (economy value added) to measure the financial performance of farmers eucalyptus oil in the working area KPHP Model Unit III Wae Tina, there are two villages in the research samples, the Village and the village of Stone Jungku Pela. Eucalyptus oil processing performed by farmers artisans in both villages are still in the scale of household businesses with simple processing techniques, and the resulting oil production is still very limited. Thus also influence the level of prosperity and stability craftsmen farmers financially. Yields of eucalyptus leaves which are then processed into eucalyptus oil by local farmers, in terms of financial yield considerable benefits for farmers and landowners employees who worked as eucalyptus oil processing. From the calculation of economy value added (EVA) obtained value is 301 222 845, where the results showed that the economy added value is greater than zero (EVA> 0). This means that companies in this case eucalyptus oil farming communities that are part of the Model Unit III Wae KPHP Tina in business operations run eucalyptus oil are added value. In other words, eucalyptus oil business is conducted with the production and distribution of products can be quite good because it can produce added value for entrepreneurs that can serve as indicators to measure the success and future business continuity.